‘Idleness Breeds Disgust for the Cell’: Circumscribing Sloth, Acedia and Health in Anchoritic Literature - Perk, Godelinde Gertrude (Nordic Journal of English Studies, 2022)
<span style="color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In medieval England, devout individuals—women in particular—self-isolated professionally, living confined to little rooms attached to parish churches. Although discomfort constituted the heart of this vocation, guides written for these anchorites also envisage enclosure as bringing risks to physical and mental health. These risks map onto <em style="box-sizing: border-box; color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">acedia<span style="color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> and sloth, two overlapping sins against which these texts caution. I argue that the anchoritic cell as metaphor and matter mediates the anchoritic endeavour of generating <em style="box-sizing: border-box; color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">acedia<span style="color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> and sloth and overcoming them. Twinning a literary approach with a feedback model from cognitive behavioural therapy, my discussion juxtaposes two texts addressing female anchorites, the thirteenth-century <em style="box-sizing: border-box; color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Ancrene Wisse<span style="color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">, and <em style="box-sizing: border-box; color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The Form of Living<span style="color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> by Richard Rolle (1300–1349) with two texts by female anchorites, <em style="box-sizing: border-box; color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">A Revelation of Purgator<span style="color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">y by an anonymous fifteenth-century anchorite and <em style="box-sizing: border-box; color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">A Revelation of Love <span style="color: rgba(0, 0, 0, 0.84); font-family: ’Noto Sans’, ’Noto Kufi Arabic’, -apple-system, ’system-ui’, ’Segoe UI’, Roboto, Oxygen-Sans, Ubuntu, Cantarell, ’Helvetica Neue’, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">by Julian of Norwich (ca. 1343–ca. 1416). It probes whether, in these texts, the cell shifts the dynamics of the feedback loop from self-reinforcing to self-stabilizing or maintains these self-reinforcing dynamics. This discussion concludes by examining the stakes involved in the texts’ commitment to the cell’s ascetic materiality. Charting parallels to the home during COVID-19 lockdowns and historicizing the gendered physical and mental effects of (self-)isolation in narrow spaces, this analysis of medieval enclosure resonates with modern concerns about how confined spaces materialize power.